CPC-151 Type of Cancer and Risk Factors in HIV Patients on Antiretroviral Treatment. (12th March 2013) - Gasanz, I; Moriel, MC; Corrales, L; Miguel, P San; Vazquez, MJ; Segura, M; Rubio, B; Calderon, C; Catalá, RM
Abstract : Background: HIV infection is associated with increased risk of cancer: AIDS-defining cancers (ADC): Kaposi's sarcoma (KS), non-Hodgkin lymphoma (NHL), cervix cancer. non-AIDS-defining cancers (NADC): Hodgkin lymphoma (HL), anal cancer, lung, head, neck, hepatocarcinoma. Purpose: To analyse patients with antiretroviral therapy and chemotherapy, type of cancer and associated risk factors. Materials and Methods: Descriptive study of patients with antiretroviral and chemotherapy between 2004–2011, extracting data from medical records and the Farmatools programme, analysing using SPSS 11.0. Results: 33 patients were obtained (3.7% of all HIV patients on antiretroviral treatment); 82% men: 16 with ADC (11 NHL, 3 KS, and 2 with NHL and KS) and 17 with NADC (5 HL, 3 lung cancer, 3 head-neck, 3 anal, 1 ovary, 1 gastric and 1 chronic lymphocytic leukaemia). When cancer was diagnosed patients presented: CD4<200 cells/microliter (27.3%), detectable viral load (VL) (33.3%), C3 category (63.6%), smokers (63.6%), human papillomavirus (HPV) (6.1%), Epstein Barr virus (21.2%), human herpes virus 8 (HHV8)(21.2%), hepatitis B-C (48.5%), intravenous drug addict (24.2%). 8 patients died. 80% KS patients and 66.7% head-neck cancer had CD4<200 (P = 0.036). 62.5% of those who died presented CD4<200 (P = 0.009). 66.6% of anal cancer patients presented HPV (P = 0.006). 100% of KS presented HHV8 (P = 0.002). Conclusions: 3.7% of HIV patients on treatment developed neoplasms, more than 50% were NADC, of which 88% started in patients with an undetectable VL, confirming a nice immunological status when cancer was diagnosed. No conflict of interest.